2021
DOI: 10.1186/s13098-021-00640-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin C supplementation on lipid profile of type 2 diabetic patients: a systematic review and meta-analysis of clinical trials

Abstract: Background and aims We conducted a systematic review and meta-analysis of clinical trials evaluating the role of vitamin C supplementation on lipid profiles among diabetic patients to summarize the available findings. Methods A comprehensive search of PubMed, ScienceDirect, Google Scholar, and Cochrane Library databases was performed. Clinical trials conducted on adult type 2 diabetic patients evaluating the effect of vitamin C supplementation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Previous studies show that supplementation of zinc (Ranasinghe et al 2015), vitamin-B3 (niacin) (McKenney 2004), and vitamin-D (Jafari et al 2016) improve cholesterol levels, suggesting the possibility that those who take these vitamin/mineral supplements are less likely to be diagnosed with dyslipidemia. But there seems to be no adequate evidence to support vitamin C and vitamin E supplementation for dyslipidemia (Hendarto et al 2019;Tareke and Hadgu 2021). We did not find any studies that demonstrated that vitamin/mineral supplementation increased the incidence of dyslipidemia.…”
Section: Taking Vitamin/mineral Supplementsmentioning
confidence: 54%
“…Previous studies show that supplementation of zinc (Ranasinghe et al 2015), vitamin-B3 (niacin) (McKenney 2004), and vitamin-D (Jafari et al 2016) improve cholesterol levels, suggesting the possibility that those who take these vitamin/mineral supplements are less likely to be diagnosed with dyslipidemia. But there seems to be no adequate evidence to support vitamin C and vitamin E supplementation for dyslipidemia (Hendarto et al 2019;Tareke and Hadgu 2021). We did not find any studies that demonstrated that vitamin/mineral supplementation increased the incidence of dyslipidemia.…”
Section: Taking Vitamin/mineral Supplementsmentioning
confidence: 54%
“…At least partly based on its antioxidant properties, AA has been considered as a complementary nutritional treatment for T2DM. However, evidence for the significance and beneficial effect of AA in T2DM has thus far been inconclusive [ 8 , 9 ]. We suspect that one reason for this inconclusive evidence is that combined genetic and dietary factors may greatly influence AA effects on metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…WAT actively regulates whole-body energy homeostasis by storing lipids and secreting adipokines [ 6 ], and HFD-induced obesity is typically associated with increased fat deposition in WAT, induction of WAT inflammation, dysregulation of adipokines, ectopic fat accumulation, and finally T2DM [ 7 ]. However, clinical trials examining the effects of AA on T2DM have thus far been inconclusive [ 8 , 9 ]. We suspect that beneficial effects of AA on metabolism might be influenced by combinations of genetic and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Although observational evidence suggested that serum vitamin C was associated with reduced BP [38,39], meta-analysis of trials found no effects of vitamin C supplementation on BP [40]. Furthermore, recent meta-analyses of randomized trials found that vitamin C supplementation was not associated with TC, TG, LDL, HDL [40][41][42], glucose, HbA1c and insulin [40,43], in line with the findings from multiple MR studies that circulating vitamin C level did not change lipids, BMI, BP [44] and glycemic traits [45]. For vitamin E, MR evidence showed that circulating vitamin E was not associated with BMI, or glucose traits [46].…”
Section: Discussionmentioning
confidence: 99%